From domination to communicative action: shifts in Madurese communication ethics - Aminullah; Rorom Ika Putri, Mufatihatuttaubah (Faculty of Communications Science, Dr. Soetomo University, 2025)
The philosophy of Bhuppa' Bhappu' Ghuru Rato is the core of Madurese culture, which emphasises respect for elders, teachers, and leaders as the basis of social hierarchy and communication ethics. Amidst modernisation and the development of digital technology, these traditional values face challenges in adapting to increasingly egalitarian patterns of global communication. This study describes the transformation of power structures in communication and analyses its impact on communication ethics, social relations, cultural identity, and the integration of local values in the modern era. This study uses qualitative methods with an ethnographic approach, through observation, interviews, and documentation of cultural and community leaders in Madura. The analysis is descriptive in order to process, categorise, and interpret data relevant to the research focus. The results show that education, both formal and informal, is a key strategy in maintaining the sustainability of this philosophy. Digital technology also plays a role as a medium for cultural preservation, as long as the narrative remains authentic and contextual. A participatory approach through communities and cultural arts has proven effective in integrating local values into modern communication practices. Therefore, synergy is needed between the government, educational institutions, cultural communities, and media actors to create a digital space that is inclusive of local narratives. This study confirms that the philosophy of Bhuppa' Bhappu' Ghuru Rato can be transformed into a framework for adaptive ethical dialogue, reflecting the cultural resilience of Madura in facing the challenges of globalisation without losing its values.